An Investigation into Teachers’ Beliefs and Practices regarding Using L1 in Teaching English at Yen Dung 1 High School, Bac Giang = Nghiên cứu về tín niệm và việc sử dụng tiếng mẹ đẻ của giáo viên trong giảng dạy tiếng Anh tại trường THPT Yên Dũng 1, Bắc - Đào, Thị Ngân, 1981- (University of Languages and International Studies, 2017)
51 p. + CD-ROM + Tóm tắt